2019
DOI: 10.1097/scs.0000000000004958
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Clinical Outcomes of Buccal Advancement Flap Versus Platelet-Rich Fibrin Application for the Immediate Closure of Acute Oroantral Communications

Abstract: The aim of this study was to compare the clinical outcomes of buccal advancement flap surgery to platelet-rich fibrin (PRF) application for the closure of acute oroantral communications (AOACs). In 36 patients, following the extractions of posterior maxillary teeth, AOACs which were larger than 3 mm diameter were detected. In group A, PRF clots were used in 21 patients and group B, classic buccal advancement flap was used in 15 patients. Baseline variables such as pain, the analgesic doses are taken, and swell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
3
10
1
Order By: Relevance
“…The ndings reported also con rm the hypothesis of signi cant differences with regard to the presence of pain and the use of painkillers taken between the two groups. This is consistent with the ndings of Bilginaylar using platelet-rich brin for oroantral communication closure and may either be attributed to the less invasive treatment protocol or to the anti-in ammatory activity and immune regulation effects of the platelet-rich brin content [15]. Pain reduction was also reported in separate clinical studies of…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The ndings reported also con rm the hypothesis of signi cant differences with regard to the presence of pain and the use of painkillers taken between the two groups. This is consistent with the ndings of Bilginaylar using platelet-rich brin for oroantral communication closure and may either be attributed to the less invasive treatment protocol or to the anti-in ammatory activity and immune regulation effects of the platelet-rich brin content [15]. Pain reduction was also reported in separate clinical studies of…”
Section: Discussionsupporting
confidence: 88%
“…However, although the ndings of the present study as well as the results of the previous studies of Blingalar, Gülesen and Agarwallse have indicated high success rates, there is controversial information about the number and the form of PRF clots to be used [15,23,24]. The smallest numbers of platelet-rich brin clots were used by Biligalyr using only two platelet-rich brin clots pressed into plugs [15]. In obvious contrast, the largest number of 6 clots was used by Gülden who also reported a successful healing process [23].…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…36 In the settings of oroantral communication, a previous study reported that the administration of PRP was significantly associated with pain relief and reduced swelling, in addition to accelerated wound healing when compared to the outcomes of buccal advancement flap. 37 Demetoglu et al furtherly reported that in cases of oroantral communication (≤5 mm), a platelet-rich fibrin membrane can be used to manage these cases. 38 Osteoradionecrosis of the jaw was also previously reported to be effectively managed by the administration of PRP.…”
Section: Efficacy Of Prp In the Different Maxillofacial Surgeriesmentioning
confidence: 99%
“…The treatment of OAC depends on the size of the communication and it is usually achieved by buccal advancement flaps. PRF clots enhance wound closure and reduce pain and swelling compared to buccal advancement flap (104). In addition, PRF membrane could be used to manage OAC of size ≤ 5 mm (105).…”
Section: Regenerative Properties Of Platelet Granulesmentioning
confidence: 99%